Discharge against medical advice among neurological patients: Characteristics and outcomes. (24th June 2020) - Raja, Aishwarya; Trivedi, Parth D.; Dhamoon, Mandip S.
Abstract: Objective: To study characteristics and outcomes of patients with stroke, traumatic brain injury (TBI), and epilepsy with discharge against medical advice (DAMA). Data Sources/Study Setting: Retrospective analysis of the 2013 Nationwide Readmissions Database, a nationally representative inpatient administrative dataset. Study Design: Associations between predictors and DAMA at index admission were analyzed using adjusted logistic models. We examined 30‐day all‐cause readmissions. Data Collection Methods: Patients aged ≥18 years at index admission for International Classification of Diseases‐9 diagnosis code of epilepsy, TBI, or stroke were included. Principal Findings: Discharge against medical advice occurred in 1998/58278 patients (3.43 percent) in the epilepsy group, 1762/211 213 (0.83 percent) in the stroke group, and 1289/74 652 (1.73 percent) in the TBI group. Factors consistently associated with increased likelihood of DAMA included lower age, male sex, non‐Medicare and nonprivate insurance, lower socioeconomic status, and behavioral risk factors (smoking history, alcohol history, and drug use). The crude 30‐day all‐cause readmission rate for those with DAMA from their index admission was 16.4 percent for the stroke cohort, 13.9 percent for epilepsy, and 13.4 percent for TBI. DAMA at index admission was significantly associated with increased risk of 30‐day all‐cause readmission among all groups (adjusted odds ratio 1.79, 95% CI: 1.65‐1.94, P  < .0001). Conclusions: Age, sex, insurance status, socioeconomic status, and behavioral factors were associated with DAMA in neurological patients. Further research is needed to develop interventions to reduce DAMA in high‐risk groups.